2 | = | 6 |

| |

x | 18 |

Cross multiply:
2 * 18 = x * 6
Simplifying
2 * 18 = x * 6
Multiply 2 * 18
36 = x * 6
Reorder the terms for easier multiplication:
36 = 6x
Solving
36 = 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
36 + -6x = 6x + -6x
Combine like terms: 6x + -6x = 0
36 + -6x = 0
Add '-36' to each side of the equation.
36 + -36 + -6x = 0 + -36
Combine like terms: 36 + -36 = 0
0 + -6x = 0 + -36
-6x = 0 + -36
Combine like terms: 0 + -36 = -36
-6x = -36
Divide each side by '-6'.
x = 6
Simplifying
x = 6